Variation in the thermal and dehydration regime below Central America: Insights for the seismogenic plate interface - Rui Qu; Yingfeng Ji; Lijun Liu; Weiling Zhu; Ye Zhu; Chaodi Xie; Shoichi Yoshioka; Haris Faheem; Lin Ding (iScience, 2023)
Summary: Slow earthquakes predominant in Costa Rica indicate unstable faulting of segmented Central American megathrusts, but the recurrence of episodic tremors and slips reported to precede a giant earthquake remains still enigmatic. The underlying mechanism is related to the variation in the coupling along the heterogeneous subduction interface which is poorly understood. In this study, we used up-to-date 3D thermal modeling to provide insights into the along-strike variation in the thermal state and hydraulic distribution beneath the Central American subduction zone. Our results show that the subducted Cocos Plate is much warmer than previously estimated, and the slab geometry exhibits remarkable perturbations along the trench. We found that the regions of large dehydration rate along the slab are consistent with the seismicity occurrence depth beneath the Moho. Below the Nicoya Peninsula and the Guatemala-Nicaragua segment of megathrusts, fluids derived from subducted slab result in increased pore fluid pressures and subsequent recurrence of slow slip events and regular earthquakes.